Strategies for Improving Banana Agroindustry Performance at Minions Winner MSMEs: A Balanced Scorecard Approach - Indra Bagaskara; Fanny Widadie; Minar Ferichani (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
Micro, small and medium enterprises are experiencing rapid development. MSMEs need to measure performance to determine business conditions and increase competitive advantage. Minions Winner MSME is a banana chip agro-industry business that has development potential. This study aims to determine the business performance of UMKM Minions Winner based on the balanced scorecard perspective and determine the business improvement strategy plan for UMKM Minions Winner. The research was conducted at MSME Minions Winner in Karanganyar Regency, Central Java using the basic descriptive method. The data sources of this research are primary data and secondary data. Analysis of research data using the balanced scorecard method. The results showed that the performance of Minions Winner MSMEs had a score of 88.5% in the good category. The financial, customer, and learning and growth perspectives achieved good performance, while the internal business process perspective was in the poor category. Indicators that are still lacking are customer acquisition, innovation level, and damaged products. Strategic recommendations suggested for improving the performance of Minions Winner MSMEs focus on internal business process perspectives and customer perspectives, including digital marketing, consignment, expansion of marketing areas, innovation of flavour variants, improvement of SOPs, elimination of job rolling systems, and monitoring.